Connecting the senior citizens with ICT: the development of Portal Komuniti Kita - Nor Fariza Mohd Nor; Fuzirah Hashim; Supyan Husin; Jamaluddin Aziz (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
The rapid growth of ICT experienced by many developed countries has brought about challenges to these governments to narrow the digital divide that exists between citizens of the country. The challenges faced by these governments reflect those faced by Malaysia. In embracing these challenges, the Malaysian government has put in tremendous effort towards building a development-oriented information society for all to enable Malaysian to access, utilize and share information and knowledge. This can be seen in the remarkable progress made towards a developed nation through the informatization strategy. However, certain groups of the population, in particular, the senior citizens are left behind in ICT, due to fear of technology, low or zero ICT literacy, lack of supporting infra and info-structures and community readiness. This paper reports on the process of developing a portal, aptly named Portal Komuniti Kita, focusing on the senior citizens. The study will also report on feedback received from a group of senior citizens who participated in the User Acceptance Test which was conducted in 2012. The development of Portal Komuniti Kita has been commissioned by the government with the aim of developing a portal for various groups of Malaysian citizens: children, teenagers, youth, women, senior citizens, people with special needs, small medium entrepreneur, and the indigenous people.